UTHM Foodie: Cafe Food Ordering System - Subramaniam, Vimalla; Mohd Yasin, Suhaila (Applied Information Technology And Computer Science, 2024)
UTHM Foodie: Cafe Food Ordering System streamlines the food ordering experience at Secangkir Cafe in Universiti Tun Hussein Onn Malaysia. The app aims to address issues related to long queues, enhancing customer satisfaction. It offers an online platform where customers can monitor their order status and receive notifications when their food is ready. Digital receipts prevent errors associated with manual ordering, ensuring a smooth process. The app features a digital menu for easy browsing, allowing customers to access detailed information about the restaurant’s offerings. Staff can manage the menu, and a sign-up/login feature prioritizes user privacy. The chosen prototyping model facilitates easy guidance and maintenance. Ultimately, the application improves efficiency, benefiting both Secangkir Cafe staff and customers, potentially attracting more regular customers and boosting sales.